Baicalein Long-Circulating Liposomes Improve Histological and Functional Outcomes After Traumatic Brain Injury - Dong Yuan; Wenbo Xu; Faisal Raza; Hajra Zafar; Shuangxian Guan; Zhen Wang; Kamran Hidayat Ullah; Hongchao Shi (Advances in Pharmacological and Pharmaceutical Sciences)
High mortality and disability have been principally linked with traumatic brain injury (TBI) with this condition being a principal issue in public health. Currently, there is no reliable pharmaceutical agent to salvage the damage caused by TBI. Baicalein (BCL), a traditional Chinese medicine active ingredient, has preliminarily shown repair activity on brain injury. However, BCL has poor water solubility and bioavailability, which culminates in rapid elimination in vivo. Herein, we sought to solve the above-mentioned challenges that are associated with the application of this flavonoid by preparing BCL-loaded long-circulating liposomes (BLC-Lips) via thin-film hydration method. Subsequently, BLC-Lips were applied to TBI model mice to evaluate their effect on brain injury repair. The results showed that the prepared BLC-Lips exhibited smaller sized nanoparticles, excellent polydispersed index (PDI), and zeta (ζ)-potential with stable property. After loading of BCL into the liposomes, we estimated the physicochemical properties of BLC-Lips to be roughly 87.98% (encapsulation efficiency [EE]) and 7.56% (loading capacity of the drug). Administration of BLC-Lips through oral route increased aqueous solubility, bioavailability, and time for in vivo circulation of BCL. Moreover, the BLC-Lips could improve outcomes of histological and neurological motor function and reduce inflammatory cytokines and neurotoxicity after TBI. Taken together, the long-circulating liposomes may serve as a new approach to potentially prolong drug circulation in vivo and increased bioavailability of BCL for TBI treatment.